Effects of fertilizer under different dripline spacings on summer maize in northern China - Li, Ge; Bai, Youlu; Wang, Lei; Lu, Yanli; Zhang, Jingjing; Zhang, Yinjie (Scientific reports, 2021)
Maximizing grain yields with effective fertilization technologies and minimizing nitrogen losses is essential in agroecosystems. In this research, we conducted a two-year field experiment to explore whether dripline spacing and fertilization rate would affect maize grain yield. Two dripline spacings (i.e., one drip line per row of maize with a row space of 60 cm and one drip line per two rows of maize) and two fertilization rates (i.e., high fertilization level: N, 180 kg ha −1 ; P 2 O 5 , 90 kg ha −1 ; and K 2 O, 90 kg ha −1 and low level: N, 139.5 kg ha −1 ; P 2 O 5 , 76.5 kg ha −1 ; and K 2 O, 76.5 kg ha −1 ) were employed in this research. The results showed that maize yield was significantly affected by both dripline spacing and fertilization rate. The maize yield was 10.2% higher in the treatment with one drip line per two rows than that in the treatment with one drip line per row. Maize yield increased by 10.9% at the high fertilization level compared to that at the low fertilization level. The quantity of cumulative ammonia volatilization was reduced by 15.1% with one drip line per two rows compared to that with one drip line per row, whereas it increased by 26.9% at the high fertilization level compared with that at the low fertilization level. These results indicated that one drip line per two rows with a high fertilization rate increased the yield and could reduce the environmental burden, which may be economically beneficial and environmentally sound for maize fertigation for green agricultural development.